2011
DOI: 10.1371/journal.pone.0020008
|View full text |Cite
|
Sign up to set email alerts
|

Study of Histopathological and Molecular Changes of Rat Kidney under Simulated Weightlessness and Resistance Training Protective Effect

Abstract: To explore the effects of long-term weightlessness on the renal tissue, we used the two months tail suspension model to simulate microgravity and investigated the simulated microgravity on the renal morphological damages and related molecular mechanisms. The microscopic examination of tissue structure and ultrastructure was carried out for histopathological changes of renal tissue morphology. The immunohistochemistry, real-time PCR and Western blot were performed to explore the molecular mechanisms associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 50 publications
1
20
0
Order By: Relevance
“…Mitochondrial dysfunction has been reported to contribute to vascular oxidative stress and vasoreactivity alterations (3436). Although further evidence is needed, structural changes in mitochondria have been found in simulated microgravity, and mitochondrial disassembly in vascular endothelial cells (24), mitochondria swelling and vacuolation in the kidney (37), and higher mitochondrial volume densities and mitochondria‐to‐myofibril ratios in myocardium (38) have been observed. However, evidence of mitochondrial dysfunction remains scare, and whether dysfunctional mitochondria contribute to vascular oxidative stress injury is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondrial dysfunction has been reported to contribute to vascular oxidative stress and vasoreactivity alterations (3436). Although further evidence is needed, structural changes in mitochondria have been found in simulated microgravity, and mitochondrial disassembly in vascular endothelial cells (24), mitochondria swelling and vacuolation in the kidney (37), and higher mitochondrial volume densities and mitochondria‐to‐myofibril ratios in myocardium (38) have been observed. However, evidence of mitochondrial dysfunction remains scare, and whether dysfunctional mitochondria contribute to vascular oxidative stress injury is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Hägg et al (4) have also demonstrated that exercise downregulates overexpression of aortic HSP70 in spontaneously hypertensive rats (4), and Ding et al (31) found a reduction in renal expression of HSP70 and in cell apoptosis in kidney-impaired rats. De Moraes et al (28) proposed that increases in cardiac output during exercise, associated with renal vasoconstriction and upregulation of endothelial NOS, could enhance blood fl ow velocity and shear stress in kidney circulation.…”
Section: Discussionmentioning
confidence: 99%
“…Both transmission electron microscopy (TEM) and scanning electron microscopy (SEM) were conducted as previously described [3234]. Briefly, Escherichia coli ATCC 25922 and Staphylococcus aureus ATCC29213 were cultured overnight, 10 7  CFU ml −1 bacteria were incubated with 1 × MIC of CHAP or diluents of the same volume at 37 °C for 30 min.…”
Section: Methodsmentioning
confidence: 99%